The Top 102 Most Cited Publications Relevant to Dental Education - Yeung, Andy Wai Kan; Tanaka, Ray; Keung Leung, Wai (Current Dentistry, 2021)
BackgroundGrowth and development in dental education globally depend on effective experience sharing and advocation of evidence-based practice, preferably tested via vigorous peer evaluation.ObjectiveThis study aimed to evaluate the most cited dental education publications. The objectives were to identify the most productive entities, and the most frequently investigated themes and specialties.MethodsA keyword literature search was performed on 1st June 2020 to identify publications relevant to dental education. PubMed, Scopus, Web of Science, ProQuest, and Campbell Collaboration databases were searched. Publications that dealt with dental education were included. Irrelevant publications were manually excluded by the authors, and disagreement was resolved by the senior author. Bibliographic data of the top 102 entries (some with equal citation ranks) were obtained from Scopus and analyzed using Bibliometrix and VOSviewer for characterization of recurring contributors and themes.ResultsThe top publications included 83 original articles, 15 reviews, 3 books, and 1 online document, written by 30 different authors, with 38 publications from dental journals not dedicated to education, and with an average of 5.5 citations per year. The most productive author was William Hendrickson. The most productive institutions were from Europe and the United States. There were 11 papers focused on operative dentistry, 9 on endodontology, 4 on special care dentistry, 2 on community dentistry, 2 on periodontology, and 2 on implantology. Within the top 102 list, 21 publications focused on the stress experienced by dental students at school. A multiple ANCOVA indicates that citation counts in these highly cited publications are associated with a number of authors and document types, such as “reviews/books/online document” compared with original articles (p < 0.001).ConclusionInfluential dental education studies were published on a variety of platforms. Over the past 20 years, the field witnessed the emergence of highly cited reports/articles. Similar to influential papers in various fields, the number of authors per top-cited dental education publications appeared to be associated with high citations indicating top quality and high appreciation/acceptance of the articles involved.
Keywords: stress; psychological